2011
DOI: 10.2965/jwet.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

Modification of DHS Bioreactor Module with Oil Palm Fiber Material for Treating Domestic Wastewater

Abstract: An oil palm fiber module has been developed to modify a down-flow hanging sponge (DHS) reactor module. The objective of the proposed system is to improve two existing DHS variants of post-treatment unit for UASB treating domestic wastewater, i.e. cube-type and curtain-type sponge as domestic wastewater treatment system for developing countries. This paper describes the potential of oil palm fiber-based DHS (PF-DHS) configuration for sewage treatment. Feasibility of the PF-DHS reactor was evaluated by conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We have been developing a biological dissolved methane oxidation system using the single closed DHS reactor , which revealed that methane oxidation occurred preferentially over ammonium oxidation in the reactor; however, the interactions of methane oxidation with sulfide and organic carbon oxidation remain to be investigated. The DHS reactor has been developing as a low cost post-treatment for the anaerobic treatment process and applied to several types of wastewaters (Machdar and Faisal, 2011;Takahashi et al, 2011;Tandukar et al, 2007); thus, it is a promising method for removing dissolved methane as well as polish up the anaerobically treated effluent.…”
Section: Introductionmentioning
confidence: 99%
“…We have been developing a biological dissolved methane oxidation system using the single closed DHS reactor , which revealed that methane oxidation occurred preferentially over ammonium oxidation in the reactor; however, the interactions of methane oxidation with sulfide and organic carbon oxidation remain to be investigated. The DHS reactor has been developing as a low cost post-treatment for the anaerobic treatment process and applied to several types of wastewaters (Machdar and Faisal, 2011;Takahashi et al, 2011;Tandukar et al, 2007); thus, it is a promising method for removing dissolved methane as well as polish up the anaerobically treated effluent.…”
Section: Introductionmentioning
confidence: 99%
“…The principal objective of this research is to evaluate the performance of the thirdgeneration of downflow hanging sponge (G3-DHS) bioreactor for treatment of desludging wastewater from IPTL. DHS bioreactor was originally published in 1997 by Machdar et al [5] and has been explored for extensive time by numerous researchers [6], [7], [8], [9], [10], [11], [12] for treatment of domestic wastewater.…”
Section: Introductionmentioning
confidence: 99%